Inori: For 2 soloists and tape - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2010)
NORI für 2 Solisten und Tonband / for 2 soloists and tape ( colour film by Suzanne Stephens, 1998 ) Live recording of a performance of INORI on April 5th 1998 at the Audimax of the TechnicalCollege in Darmstadt, with Kathinka Pasveer and Alain Louafi ( dancer - mimes ),and K. Stockhausen as sound projectionist